Pharmacokinetics and pharmacodynamics of bococizumab, a monoclonal antibody to PCSK9, after single subcutaneous injection at three sites [NCT 02043301]. Issue 5 (14th September 2017) - Wang, Ellen Q.; Plotka, Anna; Salageanu, Joanne; Sattler, Catherine; Yunis, Carla
Summary: Aim: To characterize the single‐dose pharmacokinetics (PK) and pharmacodynamics (PD) of bococizumab, a monoclonal antibody inhibiting proprotein convertase subtilisin/kexin type 9 (PCSK9), administered subcutaneously (s.c.) to the abdomen, thigh, or upper arm (NCT02043301). Methods: Seventy‐five adults with low‐density lipoprotein cholesterol (LDL‐C) ≥130 mg/dL and not on background lipid‐lowering therapy were randomized (1:1:1) to a single 150‐mg s.c. dose of bococizumab administered to the abdomen, thigh, or upper arm. Blood samples for bococizumab and lipids were collected for 12 weeks postdose. Results: Plasma bococizumab concentration‐time profiles and PK parameters were generally similar across injection sites. Mean maximum observed concentration ( C max ) ranged from 8.14 to 11.9 μg/mL, and area under the concentration‐time curve (AUCinf ) ranged from 160.3 to 198.9 µg∙day/mL. The median time to C max ( T max ) ranged from 4.25 to 6.93 days. Similar LDL‐C concentration‐time profiles were observed across injection sites, with mean (% coefficient of variation) maximum reductions in LDL‐C of −57.5% (15.8), −57.0% (25.9), and −55.0% (24.1) for the abdomen, thigh, and upper arm, respectively. Adverse events (AEs) were mostly mild and generally similar across injection sites. Commonly reported AEs were upper respiratory tract infection (9.3%), headache (6.7%), and injection site reaction (6.7%). One serious AE was reported (ischemic colitis), which was not considered related to study drug. Conclusions: Similar PK profiles and robust LDL‐C reductions were observed following a single 150‐mg s.c. injection of bococizumab administered to the abdomen, thigh, or upper arm in untreated subjects with LDL‐C ≥130 mg/dL. Bococizumab was generally well tolerated following a single 150‐mg s.c. administration in this subject population.